2010
DOI: 10.1111/j.1365-3156.2009.02449.x
|View full text |Cite
|
Sign up to set email alerts
|

Antituberculosis drug‐induced hepatotoxicity is uncommon in Tanzanian hospitalized pulmonary TB patients

Abstract: SummaryData on antituberculosis drug-induced hepatotoxicity in sub Saharan Africa are limited, probably because liver function tests are not carried out routinely during tuberculosis treatment in most African countries. We monitored the liver function of 112 Tanzanian hospitalized pulmonary tuberculosis patients during the first 2 months (i.e. the intensive phase) of tuberculosis treatment. The rate of hepatotoxicity in our study was 0.9% (95% CI 0.04-4.3%). It is encouraging to find a lower rate of antituberc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
8
1
1
Order By: Relevance
“…reported an increased risk for hepatotoxicity secondary to TB therapy among hospitalized HIV‐infected patients; however, the effect of concomitant ART could not be assessed in this retrospective study of hospital records . In studies from other African settings, hepatotoxicity from TB therapy has been reported to be low . In Tanzania, the prevalence of hepatotoxicity was only 0.9% at 2 months of TB therapy .…”
Section: Discussionmentioning
confidence: 66%
“…reported an increased risk for hepatotoxicity secondary to TB therapy among hospitalized HIV‐infected patients; however, the effect of concomitant ART could not be assessed in this retrospective study of hospital records . In studies from other African settings, hepatotoxicity from TB therapy has been reported to be low . In Tanzania, the prevalence of hepatotoxicity was only 0.9% at 2 months of TB therapy .…”
Section: Discussionmentioning
confidence: 66%
“…Unexpectedly low (2%) anti-tuberculosis drug-induced hepatotoxicity was also reported in HIV-infected pulmonary tuberculosis patients from Malawi [38]. Antituberculosis drug-induced hepatotoxicity is reported to be uncommon (1%) in Tanzanian hospitalized pulmonary TB patients [39]. In contrast higher incidence of rifampicin based anti-TB DILI (17%) [28], efavirenz based HAART associated DILI (15%) [29] and concomitant HAART and anti-TB DILI (30%) from Ethiopia is reported [30].…”
Section: Discussionmentioning
confidence: 96%
“…The type and incidence of DILI display wide differences between population and geographical location [14][16]. Severe DILI due to HAART is more frequent among Hispanics compared to other populations [14].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-tuberculosis agents are the leading cause for DILI in India, in contrast to acetaminophen in the US and the UK [17][19]. The reported incidence of anti-TB therapy and/or HAART associated DILI within Africa varies greatly [10], [15], [16], [20][23]. Recent studies indicate association of pharmacogenetic variation with DILI [10], [11], [24][26].…”
Section: Introductionmentioning
confidence: 99%